Petrogenesis and zircon LA-ICP-MS U–Pb dating of newly discovered Mesoarchean gneisses on the northern margin of the North China Craton. Issue 12 (10th September 2017) - Liu, Jin; Liu, Zhenghong; Zhao, Chen; Wang, Chujie; Peng, Youbo; Zhang, Han
ABSTRACT: Geological mapping and zircon U–Pb laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) dating has identified a Mesoarchean (2857 ± 17 Ma) geological unit in the Luanjiajie area of the northern margin of the North China Craton, within the northern part of Liaoning Province, China. This unit is dominated by tonalitic and trondhjemite gneisses that form part of a typical tonalite–trondhjemite–granodiorite (TTG) rock assemblage. These Mesoarchean gneisses are enriched in Na and depleted in K, yield K2 O/Na2 O ratios of 0.34–0.50, have Rittmann index ( σ ) values of 1.54–3.04, and are calc-alkaline. They have EuN /EuN * values of 0.77–1.20 (average of 1.03), indicating that these samples have negligible Eu anomalies, and yield high LaN /YbN values (4.92–23.12). These characteristics indicate that these Mesoarchean gneisses have fractionated rare earth element (REE) compositions that are enriched in the light REE (LREE) and depleted in the heavy REE (HREE), with steeply dipping chondrite-normalized REE patterns. These gneisses are also enriched in Rb, Th, K, Zr, and Hf, and are relatively depleted in Ta, Nb, P, and Ti. In summary, the magma that formed these tonalitic and trondhjemite gneisses was most likely derived from the partial melting of lower-crustal basaltic rocks during subduction. The timing of formation (2.85 Ga) of the Luanjiajie tonalite and trondhjemite gneisses probably represents the timing of initiation of plate tectonics within the LongGang Block during a SE-directed subduction event. The presence of inherited zircons with ages of >3.0 Ga within the Luanjiajie gneisses suggests that this area may contain as yet undiscovered rocks that formed before 3.0 Ga.